Customer productivity in technology-based self-service of virtual golf simulators. Issue 1 (1st October 2014) - Kim, Taehee; Seo, Hyomin; Cheol Kim, Min; Chang, Kyungro
Abstract : Boosting productivity in the service sector is a key priority for promoting long-term growth. To have customers perform certain tasks normally undertaken by employees is an important means to improving productivity. Technological innovation has influenced business practices for several decades and many service firms, including sports service firms, are now utilising technology extensively to reduce the use of labour. This study investigates how the user's perception of technology-based self-service (TBSS)affects customer productivity and how the customer productivity evaluated by TBSS influences the customer's intentions to reuse in relation to a virtual golf simulator - a successful and seriously played game in Korea.